(untitled) (Acta Scientiarum. Biological Sciences, 2015)
Farm workers at Brazilian tobacco plantations are frequently exposed to toxic chemicals and eventually became contaminated with these products. Flumetralin is a inhibitor of axillary bud growth on tobacco and the effects of gestational exposure should be investigated since many pesticides cross the placental barrier and cause birth defects. The aim of this study was to investigate maternal and fetal effects caused by inhalation of Flumetralin. Pregnant Swiss mice inhaled Flumetralin for 10 or 20 minutes on the seventh day of pregnancy. On the 18th day, animals were euthanized and subjected to laparotomy for removal of the uterus and embryos. The uterus was weighed and the embryos were examined. Fetuses of both treatments showed visceral changes in the uterus, kidney and liver. Skeletal abnormalities included hydrocephalus and incomplete skull ossification in both groups. In addition, the treatment of 20 minutes exposure caused anomalies in the occipital bone and the 13rd rib besides internal bleeding. There was reduction in maternal weight gain and impaired intrauterine development of the fetus. The weight of heart, liver, kidneys and testicles of fetuses were significantly decreased. Inhalation of flumetralin proved to be potentially teratogenic in both treatments, with greater damage in the group treated for 20 minutes.